Réponses

  • Utilisateur Brainly
2013-05-08T17:12:48+02:00

1) f(x)=2(3x-4)(5+x²)(2x+4)

le signe de f(x) est le même que celui de g(x)=(3x-4)(x+2)

on obtient :

x         -inf          -2            4/3               +inf

f(x)             +      0      -       0        +

 

2) f(x)=-3(x²-1)(x+6)(6-x)

le signe de f(x) est le même que celui de g(x)=(x²-1)(x²-36)

on obtient :

x         -inf             -6             -1             1             6             +onf

f(x)               +        0      -       0      +     0       -     0      +